Taxing the Playing Field: Revenue Potential, Constraints, and Optimization of Recreational Sports Taxation in South Tangerang - Dhian Adhetiya Safitra; Soni Wijayanto (Indonesian Journal of Taxation and Accounting, 2026)
Purpose – This study analyzes the implementation of the Specific Goods and Services Tax (PBJT) on recreational sports in South Tangerang City following the enactment of Law No. 1 of 2022 on Central–Regional Government Fiscal Relations (HKPD Law). As a service-oriented municipality with a rapidly growing commercial sports sector, South Tangerang presents a critical case for evaluating local tax reform. It examines the revenue potential, implementation constraints, and optimization strategies adopted by the Regional Revenue Agency (Bapenda). Methods – The study employs a qualitative descriptive approach following SRQR guidelines, combining regulatory analysis, participant observation during a ten-week field placement at Bapenda South Tangerang (November 2025–February 2026), and secondary data analysis of taxpayer registration and revenue figures for the 2022–2025 period. Findings – PBJT on recreational sports has broadened the local tax base, contributing 21.8% of newly registered entertainment-tax taxpayers in 2024–2025. Revenue from arts and entertainment services grew 46.71% in 2024, the first year of PBJT implementation. However, constraints persist including low taxpayer awareness and regulatory ambiguity. To address these, Bapenda has implemented four optimization strategies: digitalization of tax reporting, intensive social media monitoring for taxpayer discovery, inter-agency data coordination, and direct field socialization. Research implications – While existing literature on the HKPD Law focuses on macro-fiscal decentralization, this study addresses the empirical gap regarding the micro-level administrative challenges of taxing specific new consumption sectors. The findings describe implementation patterns rather than causal effects. Originality – This article offers one of the first empirical accounts of PBJT implementation on recreational sports at the municipal level, combining revenue data with a qualitative assessment of administrative constraints and optimization efforts under the newly enacted HKPD Law.